Plural provision of primary medical care in England, 2002–2012. (October 2013) - Sheaff, Rod
Objectives: Health care reforms often include provider diversification, including privatization, to increase competition and thereby health care quality and efficiency. Donabedian's organizational theory implies that the consequences will vary according to the providers' ownership. The aim was to examine how far that theory applies to changes in English NHS primary medical care (general practice) since 1998, and the consequences for patterns of service provision. Methods: Framework analysis whose categories and structure reflected Donabedian's theory and its implications, populated with data from a systematic review, administrative sources and press rapportage. Results: Two patterns of provider diversification occurred: 'native' diversification among existing providers and plural provision as providers with different types of ownership were introduced. Native diversification occurred through: extensive recruitment of salaried GPs; extending the range of services provided by general practices; introducing limited liability partnerships; establishing GPs with special clinical interests; and introducing a wider range of services for GPs to refer to. All of these had little apparent effect on competition between general practices. Plural provision involved: increased primary care provision by corporations; introducing GP-owned firms; establishing social enterprises (initially mostly out-of-hours cooperatives); and Primary Care Trusts taking over general practices. Plural provision was on a smaller scale than native diversification and appeared to go into reverse in 2011. Conclusions: Although the available data confirm the implications of Donabedian's theory, there are exceptions. Native diversification and plural provision policies differ in their implications for service development.